Hispanic Serving Institutions (HSIs) role in the development of Latinx student leaders. Issue 171 (18th October 2021) - Venegas, Kristan M.
Abstract: According to the Hispanic Association of Colleges and Universities, Hispanic Serving Institutions (HSIs) are defined as colleges, universities, or system/districts where total Hispanic enrollment constitutes a minimum of 25% of the total enrollment. Due to the enrollment dependent nature of HSIs, an institution's designation may change over time. This article will include a discussion of how HSIs develop campus cultures that go beyond their designation to support the leader development of students.